2003
DOI: 10.1111/j.1749-6632.2003.tb03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent Stem Cells Identified in Multiple Murine Tissues

Abstract: Pluripotential stem cells (PSCs) have been recently described in many tissues including skeletal muscle, brain, and bone marrow. However, the true nature of these cells is still unclear, and their precise definition has yet to be determined. We hypothesized that a common, rare population of PSCs with a broad tissue differentiation potential can be identified in multiple murine tissues and that these cells are capable of transdifferentiation into cells of different primordial germ layer origins in response to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 42 publications
1
44
0
1
Order By: Relevance
“…To support this notion several studies from our and other laboratories provided direct evidence that BM stem cells are heterogenous and perhaps pluripotent. 25,[26][27][28][29] Accordingly, BM was found to contain endothelial-, 30,31 bone-, [32][33][34] skeletal muscle-, 35 cardiac-, 36,37 hepatic- [38][39][40] and neural-tissue committed stem cells 4,41 and the potential list of versatile stem cells including mesenchymal stem cells (MSC), 42 multipotent adult progenitor cells (MAPC) 43 and as recently reported germ cells 28 is continuously expanding. However, these potential candidate cells had not been characterized well at the singlecell level.…”
Section: Introductionmentioning
confidence: 72%
“…To support this notion several studies from our and other laboratories provided direct evidence that BM stem cells are heterogenous and perhaps pluripotent. 25,[26][27][28][29] Accordingly, BM was found to contain endothelial-, 30,31 bone-, [32][33][34] skeletal muscle-, 35 cardiac-, 36,37 hepatic- [38][39][40] and neural-tissue committed stem cells 4,41 and the potential list of versatile stem cells including mesenchymal stem cells (MSC), 42 multipotent adult progenitor cells (MAPC) 43 and as recently reported germ cells 28 is continuously expanding. However, these potential candidate cells had not been characterized well at the singlecell level.…”
Section: Introductionmentioning
confidence: 72%
“…SP cells were found in many other tissues , but their role, origin, contribution to local tissues and relationship with other SP cells remain largely unknown. One attractive hypothesis is that tissue-specific SP cells derive from a common, circulating stem cell that harbors in other tissues and has the potential to integrate and become a committed progenitor of that tissue (Howell et al, 2003). Because the existence of stem cells within the BM has been well demonstrated and these cells are known to circulate, it seems reasonable to hypothesize that stem cells found in other tissues might also derive from and maintain a relationship with the BM.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately the isolation strategy of spore-like stem cells was not clearly described by the authors in the original paper and thus it was not specified how these cells were isolated from adult tissues (Vacanti et al, 2001). In contrast, by employing FACS-based phenotypic analysis of single cell suspensions prepared from murine brain, blood, and intestinal epithelium, Howell et al revealed the presence of very small CD45 − Sca-1 + c-kit − cells in varying degrees that may represent universal pluripotent stem cells residing at different levels in multiple murine tissues (Howell et al, 2003). Very small stem cells with neuroblast activity were also recently found in the subventricular zone of the murine brain (Scheffler et al, 2005).…”
Section: Very Small Cells In Adult Tissuesmentioning
confidence: 99%